European Works Councils after two decades. (September 2017) - Hann, Deborah; Hauptmeier, Marco; Waddington, Jeremy
The European Works Council Directive was adopted over 20 years ago, and a voluminous body of research has developed on this relatively new institution. This article reviews the most cited literature in order to consider our state of understanding of this research field and to identify gaps in our knowledge. Most research has focused on a limited number of European Works Councils, mainly in manufacturing, and on labour actors. We still know little about the interplay between European Works Councils and other levels of employment relations, the role of management in their working and their effects on substantive employment relations outcomes. By taking stock of current knowledge, we aim to advance future directions and possibilities for research on this theme.